Clinical and Functional Genetic Characterization of the Role of Cardiac Calcium Channel Variants in the Early Repolarization Syndrome - Chen, Xiu; Barajas-Martínez, Hector; Xia, Hao; Zhang, Zhonghe; Chen, Ganxiao; Yang, Bo; Jiang, Hong; Antzelevitch, Charles; Hu, Dan (Frontiers in Cardiovascular Medicine, 2021)
Background: Early repolarization syndrome (ERS) is an inherited sudden cardiac death syndrome. The present study investigates the role of genetic variants in cardiac calcium channel genes in the pathogenesis of ERS and probes the underlying mechanisms. Methods: PCR-based next-generation sequencing was carried out using a targeted gene approach. Unrelated ERS probands carrying calcium channel variants were evaluated clinically and compared with matched healthy controls. Wild type (WT) and mutant CACNA1C genes were co-expressed with CACNB2b and CACNA2D1 in HEK293 cells and studied using whole-cell patch-clamp techniques and confocal fluorescence microscope. Results: Among 104 ERS probands, 16 carried pathogenic variants in calcium channel genes (32.2±3.9 years old, 87.5% male). The symptoms at diagnosis included syncope (56.3%), ventricular tachycardia/fibrillation (VT/VF, 62.5%), sudden cardiac death (SCD, 56.3%). Three cases (18.8%) had a family history of SCD or syncope. Eight patients (50.0%) had a single calcium gene rare variant. The other half carried rare variants in other ERS susceptible genes. Compared with controls, the heart rate was slower (72.7±8.9 vs. 65.6±16.1 bpm, *p<0.05), QTc interval was shorter (408.2±21.4 vs. 386.8±16.9 ms, **p<0.01) and Tp-e/QT was longer (0.22±0.05 vs.0.28±0.04, ***p<0.001) in single calcium mutation carriers. Electrophysiological analysis of one mutation, CACNA1C-P817S (c.2449C>T) revealed that the density of ICa was reduced by approximately 84.61% compared to WT (-3.17±2.53 vs. -20.59±3.60 pA/pF，n=11 and 15, respectively, **p<0.01). Heterozygous expression of mutant channels was associated with a 51.35% reduction of ICa. Steady-state inactivation was shifted to more negative potentials and significantly accelerated as well. Confocal microscopy revealed trafficking impairment of CACNA1C-P817S (peripheral/central intensity: 0.94±0.10 in WT vs. 0.33±0.12 in P817S, n=10 and 9, respectively, **p<0.01). Conclusions: ERS associated with loss of function (LOF) genetic defects in genes encoding the cardiac calcium channel represents a unique clinical entity characterized by decreased heart rate and QTc, as well as increased transmural dispersion of repolarization. In the case of CACNA1C-P817S impaired trafficking of the channel to the membrane contributes to the LOF.